Ethical Naturalism and Moral Twin Earth - Viggiano, Andrea (Ethical theory and moral practice, 2008)
In order to rebut G. E. Moore’s open question argument, ethical naturalists adopt a theory of direct reference for our moral terms. T. Horgan and M. Timmons have argued that this theory cannot be applied to moral terms, on the ground that it clashes with competent speakers’ linguistic intuitions. While Putnam’s Twin Earth thought experiment shows that our linguistic intuitions confirm the theory of direct reference, as applied to ‘water’, Horgan and Timmons devise a parallel thought experiment about moral terms, in order to show that this theory runs against our linguistic intuitions about such terms. My claim is that the Horgan–Timmons argument does not work. I concede that their thought experiment is a good way to test the applicability of the theory of direct reference to moral terms, and argue that the upshot of their experiment is not what they claim it is: our linguistic intuitions about Moral Twin Earth are parallel to, not different from, our intuitions about Twin Earth.